Warm-keeping vamp and preparation method thereof

By coating the wear-resistant layer composed of isophorone diisocyanate and other materials on the surface of the kraft layer, the problem of the kraft layer being easily cracked, worn or deformed after long-term use is solved, and the upper is achieved with higher wear resistance and service life.

CN119734485APending Publication Date: 2025-04-01PUTIAN APEX FOOTWEAR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411789091.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The cowhide layer is prone to cracks, wear or deformation after long-term use, which affects the service life of the shoes.

Method used

A warm upper design is adopted, in which the surface of the cowhide layer is coated with an wear-resistant layer, and the raw materials of the wear-resistant layer include isophorone diisocyanate, polyvinyl alcohol, propyl gallate, etc. Through the combination and treatment of these materials, an wear-resistant layer with high hardness, wear resistance and chemical stability is formed.

Benefits of technology

Effectively resist physical wear, extend the service life of the material, improve the wear resistance and mechanical properties of the upper, reduce wear and deformation, and extend the service life of the upper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174869010000111
    Figure BDA0005174869010000111
Patent Text Reader

Abstract

The invention belongs to the technical field of shoes, and particularly discloses a warm-keeping vamp and a preparation method. A warm-keeping vamp comprises an inner layer, a middle layer and an outer layer, the inner layer is a fiber layer, the middle layer is an EVA foaming layer, the outer layer is a cow leather layer, and the warm-keeping vamp is characterized in that the surface of the cow leather layer is coated with a wear-resistant layer, and the wear-resistant layer comprises the following raw materials in parts by weight; comprising the following raw materials in parts by weight: 30 to 35 parts of isophorone diisocyanate, 10 to 12 parts of polyvinyl alcohol, 15 to 20 parts of propyl gallate, 3 to 5 parts of triallyl isocyanate, 18 to 22 parts of modified carbon nanofibers, 3 to 6 parts of calcium carbonate, 16 to 18 parts of modified kaolin, 2 to 4 parts of trifluoropropyl methyl polysiloxane and 2 to 5 parts of sodium dodecyl benzene sulfonate. The warm-keeping vamp prepared in the invention has good strength, crack resistance and tensile strength, the probability of occurrence of cracks, wear or deformation is reduced, and the service life of shoes is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of footwear, and in particular to a thermal insulation shoe upper and a preparation method thereof. Background Art

[0002] The structure of a shoe generally includes an upper and a sole. The upper is made of multiple material elements that are stitched or bonded together to form a cavity for comfortably and securely receiving the foot. The sole structure is fixed to the lower part of the upper, generally located between the foot and the ground. The structure of the shoe is designed to provide comfort, support, protection and functionality to adapt to different wearing needs and activity types.

[0003] The upper usually includes an inner layer, a middle layer and an outer layer. The inner layer is a fiber layer, the middle layer is an EVA foam layer, and the outer layer is a cowhide layer. The fiber layer is a layer composed of synthetic fibers or natural fibers (such as cotton and wool), which can provide good air permeability, help keep the feet dry, reduce sweat accumulation, and thus improve wearing comfort. The EVA foam layer has good softness and elasticity, which can provide additional comfort. At the same time, when walking or exercising, the EVA foam layer can absorb the reaction force of the ground, reduce the impact on the feet, and provide a cushioning effect.

[0004] The cowhide layer has a certain degree of breathability, which can help keep the feet dry. It is soft and elastic, providing good protection for the feet. However, after long-term use, frequent friction or impact, or long-term exposure to a dry environment, the cowhide is prone to cracks, wear or deformation, which will affect the service life of the shoes. Summary of the invention

[0005] In order to improve the problem that cowhide is prone to cracking, wear or deformation, the present application provides a warm shoe upper and a preparation method.

[0006] The present application provides a thermal insulation shoe upper, which adopts the following technical solution: A thermal insulation shoe upper comprises an inner layer, a middle layer and an outer layer, wherein the inner layer is a fiber layer, the middle layer is an EVA foaming layer, and the outer layer is a cowhide layer. The invention is characterized in that a wear-resistant layer is coated on the surface of the cowhide layer, and the raw materials of the wear-resistant layer, in parts by weight, comprise the following raw materials: 30-35 parts of isophorone diisocyanate, 10-12 parts of polyvinyl alcohol, 15-20 parts of propyl gallate, 3-5 parts of triallyl isocyanate, 18-22 parts of modified nano-carbon fibers, 3-6 parts of calcium carbonate, 16-18 parts of modified kaolin, 2-4 parts of trifluoropropyl methyl polysiloxane, and 2-5 parts of sodium dodecylbenzene sulfonate.

[0007] By adopting the above technical solution, isophorone diisocyanate has good hardness, excellent wear resistance, good chemical resistance and light stability, can effectively resist physical wear, and is not prone to yellowing or performance degradation when exposed to ultraviolet rays or natural light for a long time, thus extending the service life of the material. Polyvinyl alcohol has good adhesion, which can enhance the adhesion between the wear-resistant layer and the substrate, prevent delamination or peeling, and improve the stability of the overall structure; it can also increase the flexibility of the material, so that the wear-resistant layer has a certain elasticity while maintaining high strength, reducing brittle fracture caused by excessive hardness, and is not prone to performance degradation or appearance changes when exposed to outdoor environments for a long time.

[0008] Propyl gallate improves the system's antioxidant properties, light stability and weather resistance, prevents the material from aging due to oxidation, and cooperates with isophorone diisocyanate and polyvinyl alcohol to improve the system's comprehensive performance. Triallyl isocyanate reacts with polyvinyl alcohol and isophorone diisocyanate to form a denser cross-linked network, which improves the hardness, wear resistance and thermal stability of the wear-resistant layer, allowing the wear-resistant layer to maintain its performance under high temperature conditions. The modified nano-carbon fiber has extremely high strength and rigidity, which can significantly improve the wear resistance and impact strength of the wear-resistant layer; it can improve the tribological properties of the wear-resistant layer, reduce the friction coefficient, reduce wear, and also has good thermal stability and chemical stability, which can improve the performance of the wear-resistant layer under high temperature and chemical environments.

[0009] Calcium carbonate is filled in the system structure to increase the hardness, wear resistance and thermal stability of the wear-resistant layer. The particles of modified kaolin can fill the voids of the material to form a denser structure, thereby improving the wear-resistant layer's ability to resist physical wear, and also improving the tensile strength and tear strength of the wear-resistant layer, enhancing its mechanical properties, making it stronger when subjected to external forces. Trifluoropropylmethylpolysiloxane has excellent chemical stability, weather resistance and UV resistance, and can protect the wear-resistant layer from damage by UV radiation in outdoor environments and maintain its stable performance. Sodium dodecylbenzenesulfonate improves the fluidity of the system, allows the components to be mixed evenly, improves the lubricity of the wear-resistant layer, reduces friction, and thus indirectly improves the wear resistance. The components are mixed evenly, improving the wear resistance, mechanical properties and thermal stability of the system, improving the durability of the wear-resistant layer, and allowing the upper to be used for a long time.

[0010] Preferably, the method for preparing the modified carbon nanofiber comprises the following steps: (1) dispersing the carbon nanofibers in a nitric acid solution and soaking them for 10-14 minutes, then dispersing them in a sulfuric acid solution and soaking them for 12-16 minutes, washing them with water, filtering them, and drying them to obtain oxidized carbon nanofibers; (2) dispersing the nano-aluminum oxide whiskers in a silane coupling agent aqueous solution, stirring at 85-90° C. and 260-300 r / min for 20-25 min, filtering, and drying to obtain pretreated nano-aluminum oxide whiskers; (3) Dispersing the oxidized nano-carbon fibers obtained in step (1) in deionized water, adding the pretreated nano-alumina whiskers obtained in step (2), ultrasonicating for 1-2 hours, filtering, drying, and then spraying the modified chitosan solution, placing under vacuum drying at 70-75° C. for 2-3 hours to obtain modified nano-carbon fibers.

[0011] By adopting the above technical scheme, nitric acid solution removes impurities on the surface of nanocarbon fibers, increases the specific surface area of ​​nanocarbon fibers, and improves their adsorption capacity. Further treatment with sulfuric acid solution introduces oxygen-containing functional groups such as carboxyl and hydroxyl groups to the surface of nanocarbon fibers. These functional groups can improve the compatibility and interfacial bonding strength of nanocarbon fibers with the matrix material, making the nanocarbon fibers easier to disperse in the solvent and avoiding agglomeration.

[0012] The silane coupling agent reacts chemically with the hydroxyl groups on the surface of the nano-alumina whiskers to form chemical bonds, thereby changing the surface properties of the whiskers, improving the compatibility and interfacial bonding between the whiskers and the matrix material, and avoiding the agglomeration of the nano-alumina whiskers.

[0013] The oxidized nanocarbon fibers and pretreated nanoalumina whiskers are mixed, and the nanoalumina whiskers can be loaded on the surface of the oxidized nanocarbon fibers to improve the wear resistance, toughness and mechanical strength of the wear-resistant layer. The combination of oxidized nanocarbon fibers and nanoalumina whiskers can effectively disperse stress, prevent the initiation and expansion of microcracks, improve the impact resistance and wear resistance of the wear-resistant layer, and reduce the damage to the coating caused by impact. Finally, the modified chitosan solution is sprayed, and the modified chitosan forms a film on the surface of the system, wrapping the oxidized nanocarbon fibers and pretreated nanoalumina whiskers, so that the oxidized nanocarbon fibers and pretreated nanoalumina whiskers are bonded together, further improving the stability of the modified performance of the oxidized nanocarbon fibers, and subsequently improving the stability of the performance of the wear-resistant layer.

[0014] Preferably, the mass ratio of the nano-carbon fiber, the nano-aluminum oxide whisker and the modified chitosan solution is 1:0.4-0.6:0.1-0.2.

[0015] By adopting the above technical scheme, the mass ratio of nanocarbon fiber, nanoaluminum oxide whisker and modified chitosan solution is further limited within a certain range, the comprehensive performance of modified nanocarbon fiber is improved, and the synergistic effect of nanocarbon fiber and nanoaluminum oxide whisker can significantly improve the wear resistance of the wear-resistant layer. Nanocarbon fiber provides high toughness and tensile strength, while nanoaluminum oxide whisker increases hardness and compressive strength. The combination of the two can effectively disperse stress, prevent the initiation and expansion of microcracks, and thus improve the wear resistance of the wear-resistant layer. Modified chitosan solution, as an adhesive, can promote the uniform dispersion of nanocarbon fiber and nanoaluminum oxide whisker in the wear-resistant layer, enhance the bonding force between materials, and the biocompatibility and antibacterial properties of chitosan also provide additional biological functions for the wear-resistant layer. Moreover, the film-forming property of modified chitosan solution, wrapping oxidized nanocarbon fiber and pre-treated nanoaluminum oxide whisker, further improves the stability of the modified performance of oxidized nanocarbon fiber, so that the wear-resistant layer has a lower wear rate, the hardness and wear resistance of the coating are improved, thereby reducing the wear rate and extending the service life of the wear-resistant layer.

[0016] Preferably, the method for preparing the modified chitosan solution comprises the following steps: dispersing chitosan in an acetic acid solution, stirring evenly, introducing nitrogen for 15-20 minutes to exhaust the air, then adding cellulose acetate and water glass at a temperature of 70-75°C, continuing stirring for 1-2 hours, and standing to obtain a modified chitosan solution.

[0017] By adopting the above technical scheme, chitosan is dispersed in acetic acid solution, and nitrogen is used to exhaust air, so as to prevent chitosan from being degraded due to oxidation in acetic acid solution, maintain the original properties of chitosan, promote the uniform dispersion of chitosan molecules in acetic acid solution, reduce agglomeration phenomenon, and thus improve the uniformity and stability of dispersion.

[0018] By adding cellulose acetate and water glass, a cross-linking reaction can occur between chitosan and cellulose acetate to form a more stable network structure. Water glass promotes the cross-linking reaction between chitosan and cellulose acetate to form a more stable network structure. In addition, the silicate ions in water glass can cross-link with the amino and hydroxyl groups of chitosan to form a three-dimensional network structure, thereby improving the thermal stability, mechanical properties, and viscosity of the system. It can be subsequently used in modified nano-carbon fibers to improve the comprehensive performance of the modified nano-carbon fibers.

[0019] Preferably, the preparation method of the modified kaolin comprises the following steps: (1) dispersing kaolin in a dimethyl sulfoxide solution, stirring at a temperature of 70-75° C. for 30-35 minutes, filtering, washing with water, and drying to obtain pretreated kaolin; (2) dispersing the pretreated graphene in anhydrous ethanol, adding silver nanowires, ultrasonicating for 5-6 hours, and drying to obtain a mixture; (3) Dispersing the pretreated kaolin obtained in step (1) in deionized water, adding the mixture of step (2) and sodium dodecyl sulfate, ultrasonicating at a temperature of 60-65° C. for 2-3 h, and drying to obtain modified kaolin.

[0020] By adopting the above technical solution, dimethyl sulfoxide molecules can be inserted into the interlayer of kaolin, resulting in an increase in the interlayer distance of kaolin, improving the dispersibility of kaolin in the matrix, and improving the properties of kaolin, such as anti-aging properties. Subsequently, it can be mixed with other materials to improve the thermal stability and mechanical properties of the material.

[0021] Pretreated graphene is mixed with silver nanowires. The silver nanowires can be loaded on the graphene surface. Graphene and silver nanowires automatically undergo hybrid assembly through interaction to form a three-dimensional layered network structure. At the same time, the graphene sheets can effectively prevent the oxidation of the silver nanowires to form a smooth three-dimensional conductive network. The resulting mixture has stable performance and good mechanical strength and wear resistance.

[0022] The pretreated kaolin, the mixture and sodium dodecyl sulfate are mixed. Sodium dodecyl sulfate can effectively improve the dispersibility of pretreated graphene and silver nanowires in aqueous media and prevent agglomeration, thereby improving the uniformity and performance of the material. The pretreated graphene and silver nanowires can be loaded in the structure of kaolin to improve the mechanical strength, wear resistance and toughness of kaolin. The lubricity and high mechanical strength of graphene, as well as the high elastic modulus and tensile strength of silver nanowires, can significantly enhance the wear resistance of the subsequent wear-resistant layer.

[0023] Preferably, the mass ratio of the kaolin, pretreated graphene and silver nanowires is 1 g:50-60 mg:0.2-0.3 g.

[0024] By adopting the above technical solution, the mass ratio of kaolin, pretreated graphene and silver nanowires is further limited within a certain range, the mechanical properties, mechanical properties and wear resistance of kaolin are improved, the pretreated graphene has good wear resistance and mechanical properties, the silver nanowires can be loaded on the graphene surface, and the graphene and silver nanowires automatically undergo hybrid assembly through interaction to form a three-dimensional layered network structure, so that the modified kaolin has good mechanical strength and wear resistance. Kaolin, pretreated graphene and silver nanowires have a synergistic effect, which significantly enhances the wear resistance, mechanical properties and mechanical properties of the subsequent wear-resistant layer.

[0025] Preferably, graphene and calcein are dispersed in deionized water, ultrasonicated for 1-2 hours, and then nano nickel and calcium oxide are added, stirred at a temperature of 90-95° C. for 2-3 hours, and dried to obtain pretreated graphene.

[0026] By adopting the above technical solution, graphene and calcein are mixed. Calcein, as an organic molecule, can interact with the surface of graphene, improve the dispersibility of graphene in the solvent, prevent its agglomeration, and thus improve the uniform distribution of graphene in the composite material.

[0027] Nano-nickel has good mechanical properties and hardness. Nano-nickel can be loaded on the surface of graphene to improve the mechanical properties and specific surface area of ​​graphene, which is helpful for the subsequent composite of graphene with other components. Calcium oxide can also be loaded on the surface of graphene to improve the thermal stability of the system and make the performance of graphene stable.

[0028] The high hardness and excellent mechanical properties of graphene can significantly improve the wear resistance of the wear-resistant layer and reduce wear. The addition of nano-nickel further enhances the hardness and wear resistance of the material, making the wear-resistant layer stronger and able to resist stronger friction and wear. In addition, the combination of graphene and calcium oxide can improve the chemical stability of the wear-resistant layer, reduce corrosion in corrosive environments, and extend the service life of the wear-resistant layer.

[0029] Preferably, the fiber layer is woven from wool fibers. The wool is cleaned, combed, spun, woven into cloth, and then shaped, shrunk, and cut to obtain the fiber layer.

[0030] By adopting the above technical solution and the fiber layer obtained by the above process, the wool is washed to remove impurities and grease, combed to make the fibers parallel, spun and woven to form a soft and fluffy cloth, which improves the comfort of wearing. The cloth formed by spinning and weaving can lock air, form a good thermal insulation layer, and improve the warmth retention effect. By combing, spinning and weaving, the wool fibers can be tightly interwoven, which improves the strength and durability of the cloth and reduces wear and tear.

[0031] Preferably, the preparation method of the EVA foam layer comprises the following steps: mixing EVA, POE, stearic acid, titanium dioxide, maleic anhydride grafted SEBS, zinc oxide, talcum powder, and masterbatch, then kneading at 150-160° C. for 7-8 minutes, adding a foaming agent, a cross-linking agent and an accelerator, granulating to form a uniform sheet material, foaming, cooling and shaping, and cutting to obtain the EVA foam layer.

[0032] By adopting the above technical scheme, the mixed use of EVA and POE improves the elasticity and toughness of the foaming layer, and the addition of maleic anhydride grafted SEBS improves the heat resistance and chemical resistance of the material, so that the foaming layer has better physical properties. The addition of zinc oxide and stearic acid improves the chemical stability of the foaming layer, reduces corrosion in a corrosive environment, and extends the service life of the foaming layer. The addition of titanium dioxide improves the light-shielding and whiteness of the foaming layer, making its appearance more beautiful. The addition of talcum powder improves the wear resistance and weather resistance of the foaming layer, making it more durable when used outdoors. The addition of a foaming agent causes the material to generate gas during the heating process, forming a porous structure, improving the lightness and cushioning properties of the material. The use of a cross-linking agent and a promoter can enhance the cross-linking degree of the material and improve the stability and durability of the foaming layer.

[0033] In a second aspect, the present application also provides a method for preparing a thermal insulation shoe upper, comprising the following steps: (1) Wear-resistant layer: isophorone diisocyanate, polyvinyl alcohol, propyl gallate, triallyl isocyanate, modified carbon nanofiber, calcium carbonate, modified kaolin, trifluoropropyl methyl polysiloxane, and sodium dodecylbenzene sulfonate are uniformly mixed, blown at a speed of 350-380 rpm to form a film to obtain a wear-resistant layer; (2) The cowhide layer is cleaned with ethanol, and then the wear-resistant layer is bonded with an adhesive, hot-pressed to obtain a composite layer, and then the EVA foam layer is bonded to the side of the cowhide layer away from the wear-resistant layer, hot-pressed, and then the fiber layer is bonded to the side of the EVA foam layer, hot-pressed to obtain a warm shoe upper.

[0034] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing thermal insulation shoe uppers. The obtained thermal insulation shoe uppers have good mechanical properties and wear resistance.

[0035] In summary, this application has the following beneficial effects: 1. The isophorone diisocyanate in this application has good hardness, excellent wear resistance, good chemical resistance and light stability, can effectively resist physical wear, is not prone to yellowing or performance degradation when exposed to ultraviolet rays or natural light for a long time, and extends the service life of the material.

[0036] 2. The modified nano-carbon fibers in this application have extremely high strength and rigidity, can significantly improve the wear resistance and impact strength of the wear-resistant layer, can improve the tribological properties of the wear-resistant layer, reduce the friction coefficient, reduce wear, and also have good thermal stability and chemical stability, which can improve the performance of the wear-resistant layer in high temperature and chemical environments.

[0037] 3. The modified kaolin particles in this application can fill the voids in the material to form a denser structure, thereby improving the wear-resistant layer's ability to resist physical wear, and also improving the tensile strength and tear strength of the wear-resistant layer, enhancing its mechanical properties, and making it stronger when subjected to external forces. DETAILED DESCRIPTION

[0038] The present application is further described in detail below with reference to the embodiments.

[0039] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0040] Preparation example of modified carbon nanofiber Preparation Example 1-1 The preparation method of modified carbon nanofiber comprises the following steps: (1) 1.2 kg of carbon nanofibers were first dispersed in 2 L of 50% nitric acid solution and soaked for 14 min, then dispersed in 2 L of 60% sulfuric acid solution and soaked for 15 min, washed with water, filtered, and dried to obtain oxidized carbon nanofibers; (2) dispersing the nano-alumina whiskers in 1.5 L of a 0.3% by mass silane coupling agent KH550 aqueous solution, stirring at 90° C. and 300 rpm for 25 min, filtering, and drying to obtain pretreated nano-alumina whiskers; (3) Disperse the oxidized nanocarbon fibers obtained in step (1) in 3 L of deionized water, add the pretreated nano-alumina whiskers obtained in step (2), ultrasonicate for 2 h, filter, dry, then spray with the modified chitosan solution, place under vacuum drying at 75 ° C for 3 h, and obtain modified nanocarbon fibers.

[0041] The mass ratio of nano-carbon fiber, nano-alumina whisker and modified chitosan solution is 1:0.6:0.1.

[0042] The preparation method of modified chitosan solution comprises the following steps: dispersing 1 kg of chitosan in 2 L of 10% acetic acid solution by mass, stirring evenly, introducing nitrogen for 20 minutes to exhaust the air, then adding cellulose acetate and water glass at a temperature of 75°C, continuing stirring for 2 hours, and standing to obtain a modified chitosan solution.

[0043] The mass ratio of chitosan, cellulose acetate and water glass is 1:0.2:0.3.

[0044] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no nano-aluminum oxide whiskers are added.

[0045] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no modified chitosan solution is added.

[0046] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of nano-carbon fiber, nano-aluminum oxide whisker and modified chitosan solution is 1:0.4:0.2.

[0047] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of nano-carbon fiber, nano-aluminum oxide whisker and modified chitosan solution is 1:0.1:0.6.

[0048] Preparation Example 1-6 The difference from Preparation Example 1-1 is that cellulose acetate is not added in the preparation method of the modified chitosan solution.

[0049] Preparation Example 1-7 The difference from Preparation Example 1-1 is that water glass is not added in the preparation method of the modified chitosan solution.

[0050] Preparation Example 1-8 The difference from Preparation Example 1-1 is that the mass ratio of chitosan, cellulose acetate and water glass is 1:0.4:0.8.

[0051] Preparation example of modified kaolin Preparation Example 2-1 The preparation method of modified kaolin comprises the following steps: (1) dispersing 1.3 kg of kaolin in 2 L of dimethyl sulfoxide solution, stirring at 75° C. for 35 min, filtering, washing with water, and drying to obtain pretreated kaolin; (2) Dispersing the pretreated graphene in 1 L of anhydrous ethanol, adding silver nanowires, ultrasonicating for 6 h, and drying to obtain a mixture; (3) Dispersing the pretreated kaolin obtained in step (1) in 3.5 L of deionized water, adding the mixture of step (2) and 0.1 kg of sodium dodecyl sulfate, ultrasonicating for 3 h at a temperature of 65° C., and drying to obtain modified kaolin.

[0052] The mass ratio of kaolin, pretreated graphene and silver nanowires is 1g:50mg:0.3g.

[0053] The preparation method of pretreated graphene comprises the following steps: dispersing 100 mg of graphene and 2 g of calcein in 1.3 L of deionized water, ultrasonicating for 2 h, adding 0.8 g of nano nickel and 0.5 g of calcium oxide, stirring at 95° C. for 3 h, and drying to obtain pretreated graphene.

[0054] Preparation Example 2-2 The difference from Preparation Example 2-1 is that no pretreated graphene is added.

[0055] Preparation Example 2-3 The difference from Preparation Example 2-1 is that no silver nanowires are added.

[0056] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of kaolin, pretreated graphene and silver nanowires is 1 g:60 mg:0.2 g.

[0057] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of kaolin, pretreated graphene and silver nanowires is 1 g:20 mg:0.6 g.

[0058] Preparation Example 2-6 The difference from Preparation Example 2-1 is that calcium oxide is not added in the preparation method of pretreated graphene.

[0059] Preparation Example 2-7 The difference from Preparation Example 2-1 is that no nano-nickel is added in the preparation method of pre-treated graphene. Example

[0060] Example 1 A thermal insulation shoe upper comprises an inner layer, a middle layer and an outer layer, wherein the inner layer is a fiber layer, the middle layer is an EVA foaming layer, the outer layer is a cowhide layer, the surface of the cowhide layer is coated with a wear-resistant layer, and the raw materials of the wear-resistant layer, by weight, comprise the following raw materials: 30 kg of isophorone diisocyanate, 12 kg of polyvinyl alcohol, 20 kg of propyl gallate, 5 kg of triallyl isocyanate, 22 kg of modified nano-carbon fiber, 3 kg of calcium carbonate, 18 kg of modified kaolin, 4 kg of trifluoropropyl methyl polysiloxane, and 2 kg of sodium dodecylbenzene sulfonate, wherein the sodium dodecylbenzene sulfonate is sodium dodecylbenzene sulfonate.

[0061] The fiber layer is woven from wool fibers. 2 kg of wool is cleaned, combed, spun, and woven into cloth. The cloth is then shaped, shrunk, and cut to obtain the fiber layer.

[0062] During the spinning process, the twist coefficient is 1.2, and the twist of single yarn and ply yarn is 800T / M. During the weaving process, the density of the warp and weft yarns are 45X45 and 108X58 respectively. The shrinkage treatment was carried out at 95°C and 95% humidity for 20 minutes. Wool fiber was purchased from Qinghe County Yuguan Wool Products Co., Ltd.

[0063] The preparation method of the EVA foaming layer comprises the following steps: mixing 20kg EVA, 18kg POE, 2kg stearic acid, 5kg titanium dioxide, 12kg maleic anhydride grafted SEBS, 3kg zinc oxide, 6kg talcum powder and 3kg masterbatch, then banburying at 160°C for 8min, adding 0.5kg foaming agent, 0.6kg crosslinking agent and 0.2kg accelerator, granulating to form a uniform sheet material, foaming, cooling and shaping, cutting to obtain the EVA foaming layer.

[0064] The foaming process is carried out at a temperature of 182°C, the foaming ratio is controlled at 140%, and it is injected into the shoe mold through an injection molding machine. Foaming; The granulation length is between 1.5-2.0 mm. The masterbatch is purchased from Dongguan Zhengtao Plastic Co., Ltd. The foaming agent is azodicarbonamide; the cross-linking agent is diisopropylbenzene peroxide; and the accelerator is dibutyltin dilaurate.

[0065] The method for preparing the above-mentioned thermal insulation upper comprises the following steps: (1) Wear-resistant layer: isophorone diisocyanate, polyvinyl alcohol, propyl gallate, triallyl isocyanate, modified carbon nanofiber, calcium carbonate, modified kaolin, trifluoropropyl methyl polysiloxane, and sodium dodecylbenzene sulfonate are uniformly mixed, blown at a speed of 350 rpm to form a film to obtain a wear-resistant layer; (2) The cowhide layer was cleaned with ethanol, and then the wear-resistant layer was bonded with an adhesive, and hot-pressed at 80°C for 0.5 min to obtain a composite layer. The EVA foam layer was then bonded to the side of the cowhide layer away from the wear-resistant layer, and hot-pressed at 80°C for 0.5 min. The fiber layer was then bonded to one side of the EVA foam layer, and hot-pressed at 80°C for 0.5 min to obtain a warm shoe upper.

[0066] The cowhide layer was purchased from Qingdao Juxi Leather Co., Ltd.; The adhesive was epoxy resin adhesive purchased from Shandong Qiyuan Chemical Co., Ltd.; The modified nano-carbon fiber was prepared by using Preparation Example 1-1; and the modified kaolin was prepared by using Preparation Example 2-1.

[0067] Example 2 A warm shoe upper, which differs from Example 1 in that the raw materials of the wear-resistant layer, in parts by weight, include the following raw materials: 35kg of isophorone diisocyanate, 10kg of polyvinyl alcohol, 15kg of propyl gallate, 3kg of triallyl isocyanate, 18kg of modified nano-carbon fiber, 6kg of calcium carbonate, 16kg of modified kaolin, 2kg of trifluoropropyl methyl polysiloxane, and 5kg of sodium dodecylbenzene sulfonate.

[0068] Example 3 A thermal insulation shoe upper, which is different from Example 1 in that the modified nano-carbon fiber is prepared using Preparation Example 1-2.

[0069] Example 4 A thermal insulation shoe upper, which is different from Example 1 in that the modified nano-carbon fiber is prepared using Preparation Examples 1-3.

[0070] Example 5 A thermal insulation shoe upper, which is different from Example 1 in that the modified nano-carbon fiber is prepared using Preparation Examples 1-4.

[0071] Example 6 A thermal insulation shoe upper, which is different from Example 1 in that the modified nano-carbon fiber is prepared using Preparation Examples 1-5.

[0072] Example 7 A thermal insulation shoe upper, which is different from Example 1 in that the modified nano-carbon fiber is prepared using Preparation Examples 1-6.

[0073] Example 8 A thermal insulation shoe upper, which is different from Example 1 in that the modified nano-carbon fiber is prepared using Preparation Examples 1-7.

[0074] Example 9 A thermal insulation shoe upper, which is different from Example 1 in that the modified nano-carbon fiber is prepared using Preparation Examples 1-8.

[0075] Example 10 A thermal insulation shoe upper, which is different from Example 1 in that the modified kaolin is prepared using Preparation Example 2-2.

[0076] Embodiment 11 A thermal insulation shoe upper, which is different from Example 1 in that the modified kaolin is prepared using Preparation Example 2-3.

[0077] Example 12 A thermal insulation shoe upper, which is different from Example 1 in that the modified kaolin is prepared using Preparation Examples 2-4.

[0078] Embodiment 13 A thermal insulation shoe upper, which is different from Example 1 in that the modified kaolin is prepared using Preparation Examples 2-5.

[0079] Embodiment 14 A thermal insulation shoe upper, which is different from Example 1 in that the modified kaolin is prepared using Preparation Examples 2-6.

[0080] Embodiment 15 A thermal insulation shoe upper, which is different from Example 1 in that the modified kaolin is prepared using Preparation Examples 2-7.

[0081] Comparative Example Comparative Example 1 A thermal insulation shoe upper, which differs from Example 1 in that modified nano-carbon fibers are not added.

[0082] Comparative Example 2 A thermal insulation shoe upper, which differs from Example 1 in that the modified nano-carbon fibers are replaced by an equal amount of nano-carbon fibers.

[0083] Comparative Example 3 A thermal insulation shoe upper, which is different from Example 1 in that modified kaolin is not added.

[0084] Comparative Example 4 A thermal insulation shoe upper, which is different from Example 1 in that the modified kaolin is replaced by an equal amount of kaolin.

[0085] Performance testing The thermal insulation uppers prepared in Examples 1-15 and Comparative Examples 1-4 were subjected to performance tests. ISO 3376 is used to measure the tensile strength and elongation of the upper. The tensile strength is the maximum force applied to the sample before the sample breaks, and the elongation is the degree of stretching of the sample during the stretching process.

[0086] The unilateral tearing force of the upper was tested according to QB-T 4198-2011 (Determination of tearing force of leather in physical and mechanical tests: unilateral tearing), with an ambient temperature of 25° C. and a relative humidity of 75%.

[0087] The stain resistance of the shoe upper is tested according to FZ-T 01066-1999 (Determination method for stain resistance of coated fabrics), no stain (level 0): no stain is observed on the coating surface; very slightly stained (level 1): slight stain, almost imperceptible; slightly stained (level 2): ​​slight stain on the coating surface, but does not affect the overall appearance; obviously stained (level 3): the stain on the coating surface is more obvious and may affect the appearance; heavily stained (level 4): the coating surface is severely stained, and the appearance is significantly affected; seriously stained (level 5): the coating surface is seriously stained, and the appearance and performance may be seriously affected.

[0088] The wear rate of the shoe upper was tested 36 times using a universal friction and wear testing machine. The test force was 25N, the rotation speed was 87r / min, the test time was 9min, and the wear rate was calculated as follows: wear rate = (mass before friction - mass after friction) / mass before friction × 100%. The test sample size was 5.5 × 5.5cm. The test results are shown in Table 1.

[0089] Table 1 Test data of embodiments and comparative examples It can be seen from Table 1 that the thermal insulation uppers prepared in Examples 1-2 of the present application have good mechanical properties, wear resistance and mechanical strength. Among them, the tensile strength of Example 1 reaches 76 MPa, the elongation at break is 120%, the unilateral tear force is 119.5 N, the stain resistance grade is 0, and the wear rate is 3.2%, indicating that the thermal insulation uppers prepared in the present application have good mechanical properties and mechanical strength, and the various components cooperate with each other to reduce cracks, wear or deformation of the upper, thereby extending the service life of the upper.

[0090] In Example 3, nano-alumina whiskers are not added to the modified nano-carbon fibers. In Example 4, modified chitosan solution is not added to the modified nano-carbon fibers. In Examples 5-6, the mass ratio of nano-carbon fibers, nano-alumina whiskers and modified chitosan solution is changed. As can be seen from Table 1, compared with Example 1, the test results of tensile strength, elongation at break, unilateral tear force, stain resistance grade and wear rate of Examples 3-4 are significantly worse than those of Examples 1-2 and Example 5, while the performance tests of tensile strength, elongation at break, unilateral tear force, stain resistance grade and wear rate of Example 6 are better than those of Example 3. -4, but worse than Example 1 and Example 5, indicating that the nano-carbon fibers provide high toughness and tensile strength, while the nano-aluminum oxide whiskers increase the hardness and compressive strength. The combination of the two can effectively disperse stress and prevent the initiation and expansion of microcracks, thereby improving the wear resistance of the wear-resistant layer. The film-forming property of the modified chitosan solution, the wrapping of oxidized nano-carbon fibers and the pretreatment of nano-aluminum oxide whiskers further improve the stability of the modified properties of the oxidized nano-carbon fibers, so that the wear-resistant layer has a lower wear rate, the hardness and wear resistance of the coating are improved, thereby reducing the wear rate and extending the service life of the wear-resistant layer.

[0091] In the modified chitosan solution of Example 7, cellulose acetate is not added, in the modified chitosan solution of Example 8, water glass is not added, and in Example 9, the mass ratio of chitosan, cellulose acetate and water glass is changed. As can be seen from Table 1, compared with Example 1, the test effects of tensile strength, elongation at break, unilateral tear force, stain resistance grade and wear rate of Examples 7-8 are significantly worse than those of Examples 1-2, while the performance tests of tensile strength, elongation at break, unilateral tear force, stain resistance grade and wear rate of Example 8 are better than those of Examples 7-8, but worse than those of Example 1, indicating that by adding cellulose acetate and water glass, a cross-linking reaction can occur between chitosan and cellulose acetate to form a more stable network structure, and water glass promotes the cross-linking reaction between chitosan and cellulose acetate to form a more stable network structure, thereby improving the thermal stability, mechanical properties and viscosity of the system, and subsequently applying to modified nano-carbon fibers to improve the comprehensive performance of modified nano-carbon fibers. Moreover, the specific mass ratio between chitosan, cellulose acetate and water glass makes the comprehensive performance of modified nano-carbon fibers better.

[0092] In Example 10, no pre-treated graphene is added to the modified kaolin, and in Example 11, no silver nanowires are added to the modified kaolin. In Examples 12-13, the mass ratio of kaolin, pre-treated graphene and silver nanowires is changed. As can be seen from Table 1, compared with Example 1, the test results of tensile strength, elongation at break, unilateral tear force, stain resistance grade and wear rate of Examples 10-11 are significantly worse than those of Examples 1-2 and Example 12, while the performance tests of tensile strength, elongation at break, unilateral tear force, stain resistance grade and wear rate of Example 13 are better than those of Examples 10-11, but worse than those of Examples 1 and Example 12, indicating that graphene and silver nanowires automatically undergo hybrid assembly through interaction to form a three-dimensional layered network structure, so that the modified kaolin has good mechanical strength and wear resistance. Kaolin, pre-treated graphene and silver nanowires have a synergistic effect, which significantly enhances the wear resistance, mechanical properties and mechanical properties of the subsequent wear-resistant layer.

[0093] In the preparation method of pretreated graphene in Examples 14-15, calcium oxide and nano-nickel are not added respectively. As can be seen from Table 1, compared with Example 1, the test results of tensile strength, elongation at break, unilateral tear force, stain resistance grade and wear rate of Examples 14-15 are significantly better than those of Example 11 but worse than those of Examples 1-2, indicating that nano-nickel has good mechanical properties and hardness. Nano-nickel can be loaded on the surface of graphene to improve the mechanical properties and specific surface area of ​​graphene, which is helpful for the subsequent composite of graphene with other components. Calcium oxide can also be loaded on the surface of graphene to improve the thermal stability of the system, so that the performance of graphene is stable.

[0094] No modified nano-carbon fiber and modified kaolin are added to Comparative Example 1 and Comparative Example 3, respectively. As can be seen from Table 1, compared with Example 1, the test results of tensile strength, elongation at break, unilateral tear force, stain resistance grade and wear rate of Comparative Example 1 and Comparative Example 3 are significantly better than those of Example 11 but worse than those of Example 1-2, indicating that the modified nano-carbon fiber has extremely high strength, improves the wear resistance and impact strength of the wear-resistant layer, improves the tribological properties of the wear-resistant layer, reduces wear, and also has good thermal stability and chemical stability, which can improve the performance of the wear-resistant layer under high temperature and chemical environment; the particles of modified kaolin can fill the voids of the material to form a denser structure, thereby improving the ability of the wear-resistant layer to resist physical wear, and also improves the tensile strength and tear strength of the wear-resistant layer, enhances its mechanical properties, and makes it stronger when subjected to external forces.

[0095] In Comparative Examples 2 and 4, the modified nano-carbon fibers were replaced with an equal amount of nano-carbon fibers, and the modified kaolin was replaced with an equal amount of kaolin. As can be seen from Table 1, compared with Example 1, the test results of tensile strength, elongation at break, unilateral tear force, stain resistance grade and wear rate of Comparative Examples 2 and 4 were significantly worse than those of Examples 1-2, but better than those of Comparative Examples 1 and 3, indicating that the modified nano-carbon fibers and modified kaolin in the present application have better mechanical properties, improve cracks, wear or deformation of the upper, and increase the service life of the shoes.

[0096] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A warm shoe upper, comprising an inner layer, a middle layer and an outer layer, wherein the inner layer is a fiber layer, the middle layer is an EVA foam layer, and the outer layer is a cowhide layer, characterized in that: The surface of the cowhide layer is coated with a wear-resistant layer. The raw materials of the wear-resistant layer, measured in parts by weight, include the following raw materials: 30-35 parts of isophorone diisocyanate, 10-12 parts of polyvinyl alcohol, 15-20 parts of propyl gallate, 3-5 parts of triallyl isocyanate, 18-22 parts of modified nano-carbon fibers, 3-6 parts of calcium carbonate, 16-18 parts of modified kaolin, 2-4 parts of trifluoropropyl methyl polysiloxane, and 2-5 parts of sodium dodecylbenzene sulfonate.

2. A thermal insulated shoe upper according to claim 1, characterized in that: The preparation method of the modified carbon nanofiber comprises the following steps: (1) Dispersing the carbon nanofibers in a nitric acid solution and soaking them for 10-14 minutes, then dispersing them in a sulfuric acid solution and soaking them for 12-16 minutes, washing them with water, filtering them, and drying them to obtain oxidized carbon nanofibers; (2) dispersing the nano-aluminum oxide whiskers in the silane coupling agent aqueous solution, stirring at 260-300 r / min for 20-25 min at 85-90° C., filtering, and drying to obtain pretreated nano-aluminum oxide whiskers; (3) Dispersing the oxidized nanocarbon fibers obtained in step (1) in deionized water, adding the pretreated nano-alumina whiskers obtained in step (2), ultrasonicating for 1-2 hours, filtering, drying, and then spraying the modified chitosan solution, placing under vacuum drying at 70-75°C for 2-3 hours, to obtain modified nanocarbon fibers.

3. A thermal insulated shoe upper according to claim 2, characterized in that: The mass ratio of the nano-carbon fiber, the nano-aluminum oxide whisker and the modified chitosan solution is 1:0.4-0.6:0.1-0.

2.

4. A thermal insulated shoe upper according to claim 2, characterized in that: The preparation method of the modified chitosan solution comprises the following steps: dispersing chitosan in acetic acid solution, stirring evenly, introducing nitrogen for 15-20 minutes to exhaust air, then adding cellulose acetate and water glass at a temperature of 70-75° C., continuing stirring for 1-2 hours, and standing to obtain the modified chitosan solution.

5. The thermal insulated shoe upper according to claim 1, characterized in that: The preparation method of the modified kaolin comprises the following steps: (1) dispersing kaolin in a dimethyl sulfoxide solution, stirring at a temperature of 70-75°C for 30-35 minutes, filtering, washing with water, and drying to obtain pretreated kaolin; (2) dispersing the pretreated graphene in anhydrous ethanol, adding silver nanowires, ultrasonicating for 5-6 hours, and drying to obtain a mixture; (3) Dispersing the pretreated kaolin obtained in step (1) in deionized water, adding the mixture of step (2) and sodium dodecyl sulfate, ultrasonicating at a temperature of 60-65° C. for 2-3 h, and drying to obtain modified kaolin.

6. A thermal insulated shoe upper according to claim 5, characterized in that: The mass ratio of the kaolin, the pretreated graphene and the silver nanowire is 1g:50-60mg:0.2-0.3g.

7. A thermal insulated shoe upper according to claim 5, characterized in that: The preparation method of the pretreated graphene comprises the following steps: dispersing graphene and calcein in deionized water, ultrasonicating for 1-2 hours, adding nano nickel and calcium oxide, stirring at a temperature of 90-95° C. for 2-3 hours, and drying to obtain the pretreated graphene.

8. The thermal insulated shoe upper according to claim 1, characterized in that: The fiber layer is woven from wool fibers. The wool is cleaned, combed, spun, woven into cloth, and then shaped, shrunk, and cut to obtain the fiber layer.

9. The thermal insulated shoe upper according to claim 1, characterized in that: The preparation method of the EVA foam layer comprises the following steps: mixing EVA, POE, stearic acid, titanium dioxide, maleic anhydride grafted SEBS, zinc oxide, talcum powder and masterbatch, then banburying at 150-160° C. for 7-8 minutes, adding a foaming agent, a crosslinking agent and an accelerator, granulating to form a uniform sheet material, foaming, cooling and shaping, and cutting to obtain the EVA foam layer.

10. The method for preparing a thermal insulated shoe upper according to claim 1, characterized in that: The steps include: (1) Wear-resistant layer: isophorone diisocyanate, polyvinyl alcohol, propyl gallate, triallyl isocyanate, modified carbon nanofiber, calcium carbonate, modified kaolin, trifluoropropyl methyl polysiloxane, and sodium dodecylbenzene sulfonate are mixed evenly, blown at a speed of 350-380 rpm to form a film to obtain a wear-resistant layer; (2) The cowhide layer is cleaned with ethanol, and then the wear-resistant layer is bonded with an adhesive and hot-pressed to obtain a composite layer. The EVA foam layer is then bonded to the side of the cowhide layer away from the wear-resistant layer and hot-pressed. The fiber layer is then bonded to the side of the EVA foam layer and hot-pressed to obtain a warm shoe upper.

Citation Information

Patent Citations

  • Anti-tear mesh cloth for sports shoes and preparation method thereof

    CN117468241A

  • Fabric for luggage and preparation method thereof

    CN118664983A